2017
DOI: 10.1186/s40360-017-0121-1
|View full text |Cite
|
Sign up to set email alerts
|

Methimazole associated eosinophilic pleural effusion: a case report

Abstract: BackgroundAdverse reactions associated to anti-thyroid drugs include fever, rash, arthralgia, agranulocytosis and hepatitis that are thought to be hypersensitivity reactions. Five cases of pleural effusion associated to thionamides have also been reported, two with propylthiouracil and three with carbimazole.Case presentationWe report here a case of a 75-year-old man admitted because of unilateral pleural effusion. The patient had a recent diagnosis of hyperthyroidism and 6 days after starting methimazole comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…There is one case report in the literature describing a pleural effusion as a result of methimazole 7. In this case, pleural aspiration did demonstrate an eosinophilic exudate; however, unlike our case, there was no peripheral eosinophilia.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…There is one case report in the literature describing a pleural effusion as a result of methimazole 7. In this case, pleural aspiration did demonstrate an eosinophilic exudate; however, unlike our case, there was no peripheral eosinophilia.…”
Section: Discussioncontrasting
confidence: 63%
“…There have been cases of vasculitis secondary to thionamides reported, with most caused by PTU. More rarely carbimazole and methimazole have been implicated 7. Drug-induced lupus has also been described 7–10.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained in the context that the methimazole led to ANCA associated vasculitis leading to pleural effusion. This differs from the Gaspar-da-Costa et al's (BMC) case, which had eosinophilic exudative effusion with likely hypersensitivity immune drug reaction, and ANCA negative work-up [3]. The Sen et al's case showed a neutrophilic predominant effusion, but there is no mention of ANCA being tested.…”
Section: Discussionmentioning
confidence: 74%
“…This is the third published case of methimazole related pleural effusion [2, 3]. In our case, the unilateral pleural effusion was initially managed in the setting of atrial fibrillation with rapid ventricular rhythm.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation